2015
DOI: 10.1097/opx.0000000000000668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lid Debridement-Scaling in Sjögren Syndrome Dry Eye

Abstract: This pilot study showed that LDS improved symptoms, ocular staining, and meibomian gland function for the group that received LDS. This indicates that LDS can aid in the management of SS dry eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 21 publications
(25 reference statements)
1
25
0
Order By: Relevance
“…As an example, there are a growing number of reports indicating that patients with refractory dry eye, including those with Sjogren’s syndrome, show significant improvement when they receive effective therapy for MGD. 3 , 11 , 12 These findings are in alignment with a statement that Wolff made in 1946 when he concluded that the meibomian glands “are essentially the glands proper to the cornea, which in the interests of vision have been moved out of the way.” 13 The clinical science to substantiate that the health of the ocular surface is indeed dependent upon healthy meibomian gland function has taken several decades to emerge. 9 , 14 – 16 The result is a growing awareness that ocular surface health cannot be sustained, optimized, or rehabilitated in the absence of a healthy meibomian gland function.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…As an example, there are a growing number of reports indicating that patients with refractory dry eye, including those with Sjogren’s syndrome, show significant improvement when they receive effective therapy for MGD. 3 , 11 , 12 These findings are in alignment with a statement that Wolff made in 1946 when he concluded that the meibomian glands “are essentially the glands proper to the cornea, which in the interests of vision have been moved out of the way.” 13 The clinical science to substantiate that the health of the ocular surface is indeed dependent upon healthy meibomian gland function has taken several decades to emerge. 9 , 14 – 16 The result is a growing awareness that ocular surface health cannot be sustained, optimized, or rehabilitated in the absence of a healthy meibomian gland function.…”
Section: Introductionsupporting
confidence: 76%
“… 17 Supplementary therapy, which includes front surface lid heating in various forms, lid margin scrubs, lid margin debridement-scaling, and additional disease comanagement, can then help maintain the improvement of gland function achieved by evacuating the gland contents. 4 , 5 , 11 , 17 , 36 The conventional method of evacuating stagnated contents is to manually express the glands. Although the procedure is effective, it is painful and needs to be repeated several times a year.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be because both groups received eyelid exfoliation treatment. Score differences between the aforementioned studies may be because Korb and Blackie26 and Ngo et al27 performed LDS, whereas Epstein et al30 performed MBE. Meibum quality was assessed with MGYLS.…”
Section: Discussionmentioning
confidence: 99%
“…10,[28][29][30][31] Concerning clinical applications of eyelid exfoliation treatment, 2 stu dies used this treatment for DED, 26,27 4 studies for blepharitis, 10,28,30,31 and 2 studies for CL discomfort. 10,29 Regarding study group intervention, 2 studies performed eyelid exfoliation treatment alone, 27,29 whereas 5 studies performed eyelid exfoliation treatment combined with antimicrobial lid scrubs composed of terpinen-4-ol 30,31 and 1,2-octanediol 28 or warm compresses. 26 Different interventions were used in the control group, such as warm compresses, 26 terpinen-4-ol, 28 1,2-octanediol, 28 LidHygenix (Optimed Ltd.), 10,29 eyelid exfoliation treatment combined with sham lid scrubs, 30 sham eyelid exfoliation treatment combined with terpinen-4-ol, 31 and no intervention.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Hyperkeratinisation is a key feature of MGD and contributes to obstruction at the orifice of the meibomian gland . It follows that removing excess keratinised material from the eyelid margin, through debridement (Figure ), improves meibomian gland function, decreases ocular surface staining and reduces ocular discomfort symptoms . Using topical anaesthetic and lissamine green prior to the debridement treatment will assist with loosening and identifying the keratinised tissue, respectively.…”
Section: Optimising Tear Film and Ocular Surface Health For Contact Lmentioning
confidence: 99%